Small sparking flies: systematics of Pholeomyia Bilimek, 1867 (Diptera: Milichiidae: Milichiinae) - Flores, Heloísa Fernandes (2021)
Milichiidae (Diptera: Schizophora) is a family of acalyptratae flies known for the fascinating kleptoparasitic biology of most of the species. Within the family, Milichiinae is the subfamily with the largest number of described species. The males of many species of the subfamily have silvery pilosity dorsally in the abdomen that makes them \"flash\", reflecting small beams of light when they swarm early in the morning. Several aspects of the systematics of the group need to be properly understood, including questions about the phylogenetic relationships between genera. Within the subfamily, Pholeomyia Bilimek has 39 described species, of which 27 occur in the Neotropical Region. The genus has not been completely reviewed so far in literature, and there are no studies establishing the phylogenetic relationships between the species or even hypotheses of monophyly of the genus based on non-homoplastic synapomorphies. Also, questions on the synonymy of Pseudomilichia with Pholeomyia still remain. Here, the evolution of Milichiinae is discussed, and a phylogenetic hypothesis of Pholeomyia based on male morphology is presented. The phylogenetic analysis included 72 terminal taxa (57 ingroup and 15 outgroup species) and used 67 morphological characters, resulting in a single most parsimonious tree under implied weights. The monophyly of Pholeomyia is recovered, and the new cladogram for the subfamily highlights the relationships between the milichiines. Our results also corroborate that Pseudomilichia is synonymous with Pholeomyia. The cladogram obtained with 57 species of the genus show four main clades, which position and species composition may find some level of adjustment with the addition of male abdomen information in the data matrix for 12 of the species included as terminals in the analysis.